Influence of Modified sio2 Nanoparticles on the Photostability of Recycled Hdpe - Zapata-Ramirez, P; Cament-Riveros, A; Moreno-Serna, V; Saavedra-Gonzalez, M (Springer, 2024)
Silica nanoparticles (SiO2) were synthesized and organically modified with hexadecyltrimethoxysilane (Mod-SiO2) to enhance their interaction with polymer. Composites from recycled high-density polyethylene (HDPE) were obtained by a melt blending method in the presence of SiO2. The properties and photostability of the new materials were studied, as well as evaluating the effect of the content and modification of nanoparticles. Before irradiation, the microhardness of HDPE/SiO2 and HDPE/Mod-SiO2 increased ca. 65% after incorporating 5 wt% of SiO2 and Mod-SiO2 into HDPE, independent of the nanoparticle modification. After irradiation, the microhardness increased for HDPE and HDPE/SiO2, which could be related to the increased degree of crystallinity of the polymers after photodegradation. In addition, nanocomposites with modified nanoparticles (HDPE/Mod-SiO2) presented higher storage modulus (E′) and loss modulus (E″) than neat HDPE and HDPE/SiO2. In general, the HDPE/SiO2 and HDPE/Mod-SiO2 nanocomposites showed lower degradation, evidenced by lower values of carbonyl index (CI) and chemiluminescence emission (CL), and higher M-v values when compared with the neat HDPE after irradiation, especially when 3 wt% of SiO2 was incorporated into HDPE. Also, the good dispersion of modified SiO2 within recycled HDPE could improve its mechanical properties and provide stability to photodegradation. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2023.